Effect of rainfall on tree stability - Lee, Daryl Tsen-Tieng (2016)
Trees are “living structures”. They all possess an above ground superstructure as well as a below ground anchoring structure. The objective of this research was to study the loads applied to the trees, and the structural and geotechnical mechanisms that can lead to uprooting of trees in Singapore. A new shallow root model (SRM) was developed and verified with field testing data from past literature. The SRM required the field greenwood moduli of rupture (MOR) to be measured for different tree species. A four-point bending and a three-point bending apparatuses were designed and built to measure greenwood MOR for eight species of trees. The saturated and unsaturated soil properties were also required for the SRM and determined using laboratory (triaxial) and field testing. To determine the tree superstructure, a new tree structural survey method (TSSM) was developed to digitize trees regardless of species. The TSSM provided above ground tree data like tree mass, centroid and drag area. This TSSM was used to survey five trees at two sites in Singapore. Laser scans were used to verify the TSSM surveys. At the two sites (Silat Avenue (SA) and Telok Blangah Rise (TBR)) instrumentation was installed to measure climatic, soil and tree deflection data in real time. This instrumentation provided data that were used to calculate the changes in the resistance to uprooting of the trees due to changes in flux boundary conditions and climatic parameters. The SRM and the existing heart root model (HRM) were used in conjunction with the TSSM data to calculate these changes. During the monitoring period it was observed that the wind speeds that were measured were small compared to the calculated critical wind speeds required to uproot the trees or cause trunk basal failures. Parametric studies were performed numerically using EXCEL, SVFLUX, SIGMA/W and ANSYS software. Using the HRM in EXCEL, it was found that based on soil strength alone, tree resistance to uprooting was reduced dramatically by small amounts of rainfall, the raising of groundwater table as well as changes in root architecture. Using the SRM in EXCEL, it was found that resistance to uprooting was more influenced by greenwood MOR, root cross-sectional area (CSA) and sinker root size and depth than soil properties. Through SIGMA/W analyses it was found that greenwood yield strains (<5%) were often exceeded before soil yield strains (>15%) were experienced. The ANSYS analysis showed that the effective area and depth of the shallow root responsible for resistance to tree uprooting was limited to a small volume around the tree trunk. The ANSYS analysis also showed that tension root cutting was most detrimental to tree stability followed by cutting of compression and perpendicular roots in that order.